2011
DOI: 10.5779/hypothesis.v9i1.205
|View full text |Cite
|
Sign up to set email alerts
|

The 'Mighty Mouse' Model in Experimental Cardiac Transplantation

Abstract: Heterotopic Vascularized Cardiac Grafts in Rodents Heterotopic transplantation was used as early as the 1940's and 50's in large animals but it wasn't until work by Abbott et al. in 1964 that the heterotopic heart transplantation (HHTX) was perfomed in rodents; the authors used rats and utilized end-to-end anastomosis of the donor thoracic aorta to the recipient abdominal aorta and donor pulmonary artery to recipient inferior vena cava (IVC) (10). Abbott's procedure resulted in restricted blood flow to the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…With the extensive development of organ transplantation, MHT has become an important tool for the study of anastomosis technique and transplantation . The main method of arterial anastomosis is CS method, which has a simple operation process and can save the operation time .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the extensive development of organ transplantation, MHT has become an important tool for the study of anastomosis technique and transplantation . The main method of arterial anastomosis is CS method, which has a simple operation process and can save the operation time .…”
Section: Discussionmentioning
confidence: 99%
“…With the extensive development of organ transplantation, MHT has become an important tool for the study of anastomosis technique and transplantation. 8 The main method of arterial anastomosis is CS method, which has a simple operation process and can save the operation time. [9][10][11][12] However, in the process of CS method, the exposure of anastomotic site is getting smaller, which cause the edge of the artery is difficult to determine at the last 1-2 stitches.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of hearts available for transplantation is very limited, rejection is a great concern and the risk of tissue rejection would never be eliminated for a recipient's lifetime. Because of this, recipients are required to use lifelong immunosuppressive medications and are continuously monitored [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Population-based clinical studies have demonstrated that although current advanced treatment modalities, including beta-adrenoceptor blockers, diuretics, and angiotensin-converting enzyme inhibitors, as well as surgical intervention procedures and mechanical assistance devices, are effective in improving symptoms and other outcomes in patients, these therapies restore neither the pathologic changes nor the functional performance of the damaged heart and have problematic complications [ 12 , 13 ]. Heart transplantation may be an effective treatment for end-stage heart failure; the applicability of this procedure, however, is seriously limited by the availability of donor hearts and the concurrent immunorejection upon transplantation [ 14 , 15 ]. Therefore, CHD remains the most prevalent cause of death, and the structural and functional restoration of the damaged heart remains a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%